Ecoenzyme Characterization of Fruit Peel Waste Mixture and Test of Antibacterial Activity against Bacteria Causing Dental Caries - Julinar Julinar; Dinii Uswati; Fahma Riyanti; Eva Musifa (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
Ecoenzyme is a product of facultative aerobic fermentation for 3 months from organic fruit and vegetable waste. In this study, ecoenzyme was made from a mixture of fruit peel waste (papaya, orange and pineapple) with the addition of 6 liters of water. Ecoenzyme products were characterized by organoleptic properties, chemical composition, enzyme activity and antibacterial activity tests against Lactobacillus acidophilus and Streptococcus mutans bacteria that cause dental caries. The results of the study show that the ecoenzyme product had a dominant orange peel sour flavor, was cloudy brown in color with a volume of 8.4 liters from 6 liters of added water. The characterization results depict that the chemical composition of ecoenzyme contained acetic acid and lactic acid with a total acid content of 2.26%, 40.45 mg/mL protein, and secondary metabolites in the form of alkaloids, flavonoids, and saponins. The activity of several enzymes from ecoenzyme was protease 0.0246 U/mL, amylase 0.0032 U/mL and lipase 5 U/mL. Antibacterial activity against bacteria that cause dental caries is included in the category of very strong against S. mutans at a concentration of 40 (% v/v) and moderate against L. acidophilus with inhibition zone diameters of 23.33 mm and 8.23 mm respectively. The Mininum Inhibitory Concentration (MIC) and Minimum Killing Concentration (MKC) values of ecoenzyme against S. mutans and L. acidophilus bacteria were 2500 ppm and 5000 ppm respectively.Keywords: ecoenzyme, fruit-peel waste, L.acidophilus, S.mutans, antibacterial